العنف ضد المرأة، صوره وآليات الحماية القانونية منه على ضوء القانون رقم 15-19لسنة 2015 - لعواد, فتيحة; حوبه, عبد القادر (University of Eloued جامعة الوادي, 2020)
تناولت الدراسة موضوع العنف ضد المرأة، وكذا مظاهر وآليات الحماية القانونية لها ضد العنف المادي والمعنوي المارس ضدها، وقد فرضت طبيعة الموضوع التطرق إلى أهم ما جاء به المشرع الجنائي الجزائري من نصوص تجرم العنف ضد المرأة بشكل صريح، وخاصة ما تعلق منه بالعنف الجسدي والعنف الجنسي واللفظي ...، حيث تشكل في مجملها مظاهر وأشكال للعنف. وقد كشفت هذه الدراسة أهم النصوص القانونية، التي استحدثها المشرع في التعديل الأخير لقانون العقوبات سنة 2015، حيث تم فيه تجريم بعض صور العنف الممارس ضد المرأة داخل الأسرة وخارجها، أبرزها العنف الجسدي واللفظي، زيادة على العنف المعنوي كالإهمال العائلي والتحرش الجنسي، وغيرها من مظاهر العنف الذي يطال المرأة في المجالين الخاص العام. ولقد شدد المشرع في العقوبة على مرتكبيها في إطار تجسيد الحماية القانونية للمرأة ضد العنف، وذلك من خلال سياسة التجريم والتشديد في العقوبة على مرتكبي أفعال العنف لاسيما المرتكب ضد المرأة. Violence against women is a real appearance of a social phenomenon. It has been widespread in recent years since the beginning of this millennium, as violence in its material and moral appearance has become a real threat to all vulnerable groups in societies. Violence against women in all its forms is also considered a crime punishable by law, which requires combating, criminalizing it, and emphasizing its perpetrators. Since violence against women is a crime recognized today locally and internationally, most laws and legislations have come to condemn it. It also recognizes its serious, health and psychological effects on women specifically. This research paper discusses the forms of physical and moral violence practiced against her, and to identify the mechanisms adopted by the criminal Algerian legislator following the recent changes taking place in the Penal Code for the year 2015 in order to combat violence.
مجلد11، عدد3
Keywords: .العنف ضد المرأة، العنف المادي، العنف المعنوي، آليات الحماية، القانون; violence against women, physical violence, moral violence, protection mechanisms, law.